1999
DOI: 10.1046/j.1469-8137.1999.00332.x
|View full text |Cite
|
Sign up to set email alerts
|

Multistrain infections of the grass Brachypodium sylvaticum by its fungal endophyte Epichloë sylvatica

Abstract: Endophytes of the genus EpichloeW (Clavicipitaceae, Ascomycota) are systemic symbionts of cool-season grasses. Their interactions with grass hosts may vary between mutualistic and pathogenic depending on the mode of endophyte reproduction. Sexual strains prevent flowering and seed set (choke disease) of the host and can be horizontally transmitted by ascospores, while asexual strains remain asymptomatic and are vertically transmitted through seeds. In Switzerland nearly all plants of Brachypodium sylvat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
36
0

Year Published

2001
2001
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 49 publications
(39 citation statements)
references
References 67 publications
3
36
0
Order By: Relevance
“…To explain this finding, it has been suggested that seed-transmitted, asexual endophytes should invest more in host protection than sexual endophytes, because asexual endophytes depend on host fitness and seed production for dispersal, while horizontally transmitted, sexual endophytes do not ). Our observations on B. sylvaticum would be consistent with such a hypothesis, assuming that flowering and stromata-forming tillers harbour genetically distinct endophyte genotypes, for which there is evidence (Meijer and Leuchtmann 1999). Of course, alkaloid content may vary in endophyte-infected wild grasses, depending on genetic, geographic or environmental factors (Agee and Hill 1994;Saikkonen et al 1998) and further studies are needed to test this hypothesis in other natural grass-endophyte associations.…”
Section: Herbivory In Natural Populationssupporting
confidence: 72%
See 3 more Smart Citations
“…To explain this finding, it has been suggested that seed-transmitted, asexual endophytes should invest more in host protection than sexual endophytes, because asexual endophytes depend on host fitness and seed production for dispersal, while horizontally transmitted, sexual endophytes do not ). Our observations on B. sylvaticum would be consistent with such a hypothesis, assuming that flowering and stromata-forming tillers harbour genetically distinct endophyte genotypes, for which there is evidence (Meijer and Leuchtmann 1999). Of course, alkaloid content may vary in endophyte-infected wild grasses, depending on genetic, geographic or environmental factors (Agee and Hill 1994;Saikkonen et al 1998) and further studies are needed to test this hypothesis in other natural grass-endophyte associations.…”
Section: Herbivory In Natural Populationssupporting
confidence: 72%
“…Surveys in Switzerland and other European countries suggest that probably almost all plants of B. sylvaticum are infected with the strictly host-specific fungus E. sylvatica (Bucheli and Leuchtmann 1996;Leuchtmann and Schardl 1998). The association is characterised by a high rate of asymptomatic, seed-transmitted infections, and only rare sexual reproduction of the fungus (Bucheli and Leuchtmann 1996;Meijer and Leuchtmann 1999). The wide distribution of E. sylvatica and the consistent infection of host plants suggest that infected plants have a substantial fitness advantage.…”
Section: Methodsmentioning
confidence: 95%
See 2 more Smart Citations
“…Sometimes impact from the environment can make these fungi parasitic or pathogenic to host plants (Schardl et al 1997;Meijer, Leuchtmann 1999;Schulz et al 1999;Kogel et al 2006;Johnson, Oelmüller 2009). Most of them are non-specific regarding their host preference (Petrini 1986;Saikkonen et al 1998;Arnold et al 2000) and can live together with other endophytes in the same host (An et al 1992;Saikkonen et al 1998;Arnold et al 2000), holding greater promise for plant growth promotion and increased yield in agriculturally important grasses.…”
Section: Introductionmentioning
confidence: 99%